Immunomodulatory effects of ulinastatin combined with continuous blood purification in sepsis: a systematic review and meta-analysis - Hui Gao; Zhiqiang Tang; Shucheng Zhao; Yuanjun Zhang (Frontiers in Pharmacology)
BackgroundSepsis involves a dysregulated immune response to infection, causing inflammation and organ dysfunction. This systematic review and meta-analysis evaluated the immunomodulatory effects of ulinastatin combined with continuous blood purification (CBP) in sepsis.MethodsThis study involved a literature search, data extraction, quality assessment, and meta-analysis to evaluate the effects of ulinastatin combined with CBP. A total of 34 studies, including 28 randomized controlled trials (RCTs) and 6 retrospective studies involving patients with sepsis, were included.ResultsThe pooled results demonstrated significant reductions in inflammatory markers including CRP (SMD: 2.210, 95% CI: 2.760 to −1.661, P < 0.0001), IL-1β (SMD: 1.536, 95% CI: 1.773 to −1.299, P < 0.0001), IL-6 (SMD: 2.679, 95% CI: 3.271 to −2.086, P < 0.0001), IL-8 (SMD: 2.959, 95% CI: 4.582 to −1.337, P < 0.0001), IL-10 (SMD: 4.449, 95% CI: 7.216 to −1.682, P = 0.002), PCT (SMD: 3.787, 95% CI: 4.597 to −2.977, P < 0.0001), TNF-α (SMD: 2.734, 95% CI: 3.480 to −1.987, P < 0.0001), and mortality (OR: 0.30, 95% CI: 0.22 to 0.42, P < 0.0001) in ulinastatin group compared with control group. Egger’s test indicated significant publication bias (P = 0.002).ConclusionUlinastatin combined with CBP significantly reduces inflammatory markers and mortality in sepsis patients, suggesting its potential benefit in managing sepsis-related inflammation. Further studies are needed to confirm these findings.